Processo de construção do conhecimento científico na educação básica a partir de experiências com robótica pedagógica - Oliveira, Ortenio de (Universidade Federal de São Carlos, 2018)
With an increasingly intense presence in daily life, technological innovations influence the way of life of society, changing behaviors and perceptions of reality. In the educational sphere, it draws attention to the need for reflections and reformulations of its teaching processes in order to meet the learning expectations of generations of students increasingly connected with the world around them. Thus, this research aims to identify and characterize the process of construction of scientific knowledge in basic education through experiences that use robotics as a pedagogical tool. To achieve this goal, the research was divided into specific objectives: 1) to identify and characterize initiatives of robotics use in the educational context; 2) to monitor and analyze how the experiences are elaborated and applied; 3) describe the most common pedagogical strategies in these experiments, identifying the most explored contents; 4) to systematize and analyze the possibilities of employment of robotics for the construction of scientific knowledge of areas not explored in the analyzed experiments; 5) explore possible relationships between pedagogical robotics and learning theories. The methodological procedures adopted to achieve the proposed objectives were divided into different stages. In the first stage, a bibliographical research was carried out, at a national level, in scientific databases, selecting theses, dissertations and the scientific production published in annals of SBC events. At the international level, articles from the Scopus and Web of Science databases complemented the bibliographical research, reporting on the contributions and challenges of pedagogic robotics, pointing out positive trends in its application in the teaching of engineering, mathematics, science and also in technological education. The second stage counted on the field research, done in institutions that perform the experiments with robotics as an integral part of the curriculum or in extracurricular activities. As results, in the first stage, we highlight the similarity between the discourses of the theme that discuss ways of implementing robotics in education, its motivational aspects and the challenges faced. International productions are more emphatic in reflecting the need for more research and, in both national and international productions, the exploration of robotics takes place both in scientific disciplines and in technological education. In the second stage, the results were promising, especially in one of the institutions, where the theme was implemented in early years of elementary education, addressing science content in conjunction with robotics activities. The students were motivated during the activities, making the classes their moment of play within the school. The teachers signaled for expansion of the activities contemplating other disciplines and the increase in the number of students participating. Other points that can be highlighted in the results, at all stages: the focus of most research involving robotics is focused on technological education, raising digital literacy to a central point in the issues involving technologies in basic education.
Process of construction of scientific knowledge in basic education from experiences with pedagogic robotics
Keywords: Robótica pedagógica; Tecnologia educacional; Ciência e tecnologia; Construcionismo; Ensino de ciências; Pedagogical robotics; Educational technology; Science and technology; Constructionism; Science teaching; CIENCIAS HUMANAS